Sosialisasi Artificial Intellegence dan Pemanfatannya dalam meningkatkan kesadaran digital remaja sekolah di MAN 4 Bojonegoro - ZAHRA MUF FARIDA EFENDI; Fahmi, Torikul; Nurkhafid; Nawawi, Ahsan; Mustofa, Salas Kamal; Biyadillah, Kafa (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The rapid development of Artificial Intelligence (AI) has significantly impacted various fields, including education, particularly among school-aged teenagers. The digital transformation driven by AI has altered learning patterns but also presents challenges such as low digital literacy, limited understanding of AI ethics, technical misuse, and weak critical thinking skills. This activity aims to improve the digital awareness and understanding of school teenagers, especially students of class X-2 at MAN 4 Bojonegoro, regarding the wise and responsible use of AI. The method used is community education through socialization, consisting of preparation, implementation, and evaluation stages involving 18 students. The evaluation was conducted through a questionnaire to assess students’ understanding and attitudes after the activity. Results showed improved comprehension of AI concepts, its benefits, risks, and the importance of digital ethics. Students were able to identify key figures, examples of AI application, and emerging careers such as prompt engineers. Most participants experienced increased digital awareness and displayed a more reflective attitude toward AI use. In conclusion, this socialization effectively enhanced digital awareness and understanding of AI ethics among school teenagers. It also highlights the importance of school support in creating a positive educational environment for technology learning.